The Influence of Audit Quality and Capital Structure on Firm Performance with Earnings Management as a Mediating Variable - Atiningsih, Suci (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2025)
Purpose: This study aims to examine the effect of audit quality on company performance with earnings management as a mediating variable. These variables consist of audit quality, capital structure, firm performance, and earnings management. The uniqueness of this study lies in the use of mediating variables in earnings management. Methodology: The data source taken is the financial statements of service companies listed on the Indonesia Stock Exchange (IDX) in 2017-2023, which were obtained through the official IDX platform. By using the purposive sampling technique, this study collected 154 data for further analysis. Findings: The results of this study indicate that audit quality and capital structure have an effect on earnings management, earnings management has a negative effect on ROA and ROE, audit quality and capital structure have an effect on ROA and ROE, and audit quality and capital structure have a direct effect on both ROA and ROE, so earnings management cannot mediate the effect of audit quality and capital structure on firm performance (ROA and ROE). Novelty: This study combines the four variables (audit quality, capital structure, firm performance, and earnings management), which is still relatively rare, so there is an opportunity to explore new relationships and how quality audits can limit earnings management and ultimately improve company performance. Also, earnings management is often used to cover up the negative impacts of certain capital structures.